2022
DOI: 10.1038/s41598-022-14201-1
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine and norepinephrine in follicular fluid synergistically enhance the antioxidant capacity of human granulosa cells and the outcome of IVF-ET

Abstract: An increasing number of studies demonstrate that changes in neurotransmitters metabolic levels in follicular fluid are directly related to oocyte maturation, fertilization, the quality of embryo and pregnancy rates. However, the relationship between the intra-follicular neurotransmitters and the function of granulosa cells (GCs), and the outcome of in vitro fertilization-embryo transfer (IVF-ET) is not clear. Human follicular fluid and cumulus GCs were harvested from large follicles obtained from patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…CREB) exhibited underexpression at this time point, regardless of their cellular or pathway position. The exception was AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) receptor, which is stimulated by glutamic acid present in follicular fluid [52] and in turn regulates signaling molecules (presumably via calcium influx) involved in ovulation [53]; AMPAR showed overexpression with all treatments. At this time, signaling was also very similar between FSH 18/21 and eq FSH with the exception of GPCRs for glycoprotein hormones and c-Jun N-terminal kinase (JNK; a kinase involved in cell cycle progression, mitosis and apoptosis [54, 55]) signaling overexpression stimulated by eq FSH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CREB) exhibited underexpression at this time point, regardless of their cellular or pathway position. The exception was AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) receptor, which is stimulated by glutamic acid present in follicular fluid [52] and in turn regulates signaling molecules (presumably via calcium influx) involved in ovulation [53]; AMPAR showed overexpression with all treatments. At this time, signaling was also very similar between FSH 18/21 and eq FSH with the exception of GPCRs for glycoprotein hormones and c-Jun N-terminal kinase (JNK; a kinase involved in cell cycle progression, mitosis and apoptosis [54, 55]) signaling overexpression stimulated by eq FSH.…”
Section: Resultsmentioning
confidence: 99%
“…CREB) exhibited underexpression at this time point, regardless of their cellular or pathway position. The exception was AMPA (αamino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) receptor, which is stimulated by glutamic acid present in follicular fluid [52] and in turn regulates signaling molecules (presumably via calcium influx) involved in ovulation [53]; AMPAR showed overexpression with all treatments.…”
Section: Information Figs S5 and S6)mentioning
confidence: 99%
See 1 more Smart Citation
“…In light of new evidence that peripheral nerves can initiate and potentiate tumor growth through delivery of neurotransmitters, such as NE ( 36 , 41 , 65 , 66 ), we considered whether NE may play a role in the progression of HGSC from the FT. We utilized immortalized human FTE cell lines with reduced TP53 expression (shTP53) ( 67 , 68 ), characteristic of HGSC precursor lesions ( 13 ), and exposed them to a physiologically relevant dose of NE ( 69 ) that is also commonly used in relevant experimental reports ( 54 , 70 ). Overall, we demonstrate that NE enhances FTE cell spheroid formation and subsequent viability in ULA culture conditions, enabling adhesion of these aggregates to the OSE.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Wang et al, has shown that Gln, synergistically with norepinephrine, promotes estrogen synthesis in FF of IVF patients, and increases the expression of antioxidant genes, as antioxidant gene IDH1, glutathione peroxidase, and Nrf2. Besides, high levels of Gln improve the function of granulose cells in vitro [ 55 ]. On the other hand, it cannot be excluded that the decrease of Gln found in patients with BC is the result of a compensatory mechanism to attenuate oxidative stress [ 56 ].…”
Section: Discussionmentioning
confidence: 99%